Legal issues in tourism development projects: text network analysis of precedents - Yeol Park, Gyung; Lee, Daechang (International Journal of Engineering and Technology, 2019)
We had investigated the structural characteristics of legal issues arising from the public tourism development projects in Korea by conducting for the first time a comparative analysis on the semantic relationships among unstructured data of keywords, which are listed in the text of precedents of courtsâ€™ ruling. Using text network analysis method, we analyzed the text networks linked or related among 140,656 words in 76 precedents of Koreaâ€™s courts from 1975 to 2015. The results showed that high level of centrality was found in the keywords like land, project operators (governors and mayors), and public welfare. These means most of legal disputes were filed against governors or mayors because of conflicting interests in lands and legitimacy of public projects and their development plans. Such explanation of structural causes was based only partially on some literatures using the traditional method of contextual analysis on some of statues themselves but now we could confirm that it was supported quantitatively and comprehensively by the text network analysis on all precedents in this paper. It implies further that Korean tourism business law needs to be amended to clarify the standards for eminent domain and complement the process of arbitration, reconciliation and mediation to minimize the cost of litigations.Â Â